Peningkatan Kesadaran Generasi Muda dalam Kegiatan Pengajian Rutin Mingguan (Studi Kasus Di Desa Sekunyit Kaur Selatan) - Lensi Puspita Sari; Ica Rozalia; Hidayatul Muniroh; Rahma Agustina; Ozi Erdianti; Eliza Pebriyani; Kesya Dwi Sartika; Ilham Taufiq Alamsyah; Agung Satiawan; Susandra; Solehudin Firdaus; Dayun Riyadi (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This study aims to analyze youth participation in regular religious study sessions before the implementation of the KKN program, identify factors influencing low participation, and develop and evaluate strategies for implementing mosque-based KKN programs to enhance their participation. Through the Asset-Based Community-Driven Development (ABCD) approach, the KKN program is expected to empower the community, increase youth engagement, and provide sustainable positive impacts. Adapting study session materials to be more interactive and relevant, and utilizing technology to reach more participants, is anticipated to lead to a significant increase in youth participation, religious understanding, and integration of religious activities with formal education. This approach aims not only to fulfill academic requirements but also to strengthen social and religious bonds within the community.